2021
DOI: 10.31234/osf.io/mbvn4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Symptom Level Perspective on Reactive and Proactive Aggressive Behaviours and ADHD Symptoms in Childhood

Abstract: Objective: Attention-Deficit/Hyperactivity Disorder (ADHD) is one of the most prevalent childhood disorders, affecting around 6.5% of youths worldwide. One common and impairing correlate of ADHD is aggressive behaviour which likely acts as a major contributor to the negative outcomes associated with ADHD. ADHD symptoms and aggression are both heterogeneous and it has been speculated that certain symptoms of ADHD might map more closely to certain types of aggressive behaviour. This study uses a symptom-level a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In brief, the z-proso cohort currently consists of a large sample of young Swiss adults (e.g., n = 1,180 for age 20 wave) who have participated in 10 waves of data collection, tracking their childhood development, since the age of seven. Participants were recruited using a stratified sampling procedure, selecting 56 schools based on school size and location to warrant sufficient representativeness across a wide range of ethnicities, socioeconomic backgrounds, and area-based deprivation (Eisner et al, 2019;Speyer, Eisner, et al, 2022). Previous investigations have indicated that the sample is largely illustrative of the underlying same-aged population (N. L. Eisner et al, 2019).…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, the z-proso cohort currently consists of a large sample of young Swiss adults (e.g., n = 1,180 for age 20 wave) who have participated in 10 waves of data collection, tracking their childhood development, since the age of seven. Participants were recruited using a stratified sampling procedure, selecting 56 schools based on school size and location to warrant sufficient representativeness across a wide range of ethnicities, socioeconomic backgrounds, and area-based deprivation (Eisner et al, 2019;Speyer, Eisner, et al, 2022). Previous investigations have indicated that the sample is largely illustrative of the underlying same-aged population (N. L. Eisner et al, 2019).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…For example, as the roles typically adopted during adulthood (e.g., obtaining jobs, fostering romantic relationships, and having children) require prosocial behaviors (e.g., empathy, perspective-taking, and responsibility), those who experience heightened aggression may struggle to gain and maintain such roles (Murray et al, 2021;Wensveen et al, 2017). Considering these findings, aggression is often considered one of the most impairing consequences of ADHD (Speyer, Eisner, et al, 2022). Thus, numerous efforts have been made to identify the underlying factors in the ADHD/aggression link that may be important to target in interventions.…”
Section: Introductionmentioning
confidence: 99%